Hybrid Repair of a Medial Meniscus Mid-Body Radial Tear - Carlos E. Franciozi MD, PhD; Enzo S. Mameri MD, MSc; Felipe C. Schumacher MD; Marcos V. Credidio MD; Marcelo S. Kubota MD; Marcus V. Luzo MD, PhD (SAGE Publishing, 2023)
Background: Meniscal radial tears are associated with altered contact mechanics, as they have the potential to disrupt the meniscal hoop stress mechanism. In prior studies, radial tears are associated with higher grade of cartilage damage, as well as higher rate and severity of meniscal extrusion in knees with a radial tear relative to other types of tears. Improved understanding of the meniscus biological potential together with modern developments in surgical technique has paved the way for the current emphasis on repairing even radial tears. Indication: Large or complete radial tears of the meniscus without prohibitive joint space narrowing or severe cartilage damage. Technique Description: A hybrid technique of meniscal radial repair is described, combining (1) 2 transtibial pullout cinch-loop sutures, (2) 2 inside-out vertical rip-stop sutures and 2 oblique sutures in a "cross-tag" configuration, and (3) 1 horizontal mattress all-inside suture. The repair is biologically augmented with a notch marrow-venting procedure. Results: Recent evidence has demonstrated significant biomechanical benefit in terms of increased load to failure and construct strength when adding transtibial tunnel augmentation to radial repairs. In addition, rip-stop sutures decrease the chance of cut-out relative to nonreinforced repairs. Those biomechanical advancements are reflected in excellent patient-reported outcomes as well as healing rates following radial repair. Discussion/Conclusion: We present a hybrid technique encompassing the most biomechanically effective novel radial repair techniques, backed by excellent clinical outcomes following radial repair in the current literature. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.